Avaliação do potencial neuroprotetor de fármacos antipsicóticos em alterações bioquímicas, moleculares e comportamentais induzidas por antagonista de receptor NMDA (MK-801) em peixe zebra (Danio rerio) - Bender, Kelly Juliana Seibt (2011)
Schizophrenia is a severe mental illness characterized by positive and negative symptoms and cognitive deficits. This pathology is still poorly understood. Reduction of glutamatergic neurotransmission by NMDA receptor antagonists mimics disease symptoms. Many animal models have shown their importance in the study of this disease and the zebrafish has been proposed as a promissor model to study the in vivo effects of several drugs and to discover new pharmacological targets. In this study we characterized the behavioral syndrome produced by the NMDA receptor antagonist, MK-801, exposure in zebrafish and investigated the ability of antipsychotic drugs to reverse the schizophrenia-like symptoms. MK-801 (20 μM) increased the locomotor behavior as measured by the number of line crossings, distance traveled, and the mean speed in the tank test after 15, 30, and 60 min of exposure. The antipsychotics sulpiride, olanzapine, and haloperidol counteracted MK-801-induced hyperactivity on all parameters analyzed and at doses that, given alone, had no effect on spontaneous locomotor activity. Modeling social interaction and cognitive impairment in animals can be of great benefit in the effort to develop novel treatments for negative and cognitive symptoms of schizophrenia. Results showed that MK-801 (5 μM) given pre-training hindered memory formation while both atypical antipsychotics sulpiride (250 μM) and olanzapine (50 μM) improved MK-801-induced amnesia. The same change was observed in the social interaction task, where atypical antipsychotics reversed the MK-801-induced social interaction deficit whereas the typical antipsychotic haloperidol (9 μM) was ineffective to reverse those behavioral deficits. Some evidence suggests that changes in the purinergic system, more specifically in adenosinergic activity, could be involved in the physiopathology of schizophrenia. In this study, we demonstrated that haloperidol treatment (9 μM) was able to decrease ATP hydrolysis (35%), whereas there were no significant changes in ADP and AMP hydrolysis in brain membranes. Adenosine deaminase activity in membrane fractions was significantly inhibited (38%) after haloperidol treatment when compared to the control group. Furthermore, haloperidol exposure also led to a decrease in NTPDase gene expression (entpd2_mq and entpd3), and adenosine deaminase (adal). Considering that the enzyme Na+,K+-ATPase is essencial to brain normal function, we evaluated the effect of MK-801 and antipsychotic drugs on activity this enzyme. Our results showed that MK-801 treatment significantly decreased Na+,K+-ATPase activity, and all antipsychotics tested prevented such effects. Moreover, it is known that oxidative stress may be associated with the physiopathology of schizophrenia and the Na+,K+-ATPase is particularly susceptible to free radical attack. We showed that MK-801 treatment did not alter reactive oxygen/nitrogen species by 2′7′-dichlorofluorscein (DCF) oxidation assay, but increased the levels of thiobarbituric acid reactive substances (TBARS), when compared to controls. The antipsychotics sulpiride, olanzapine, and haloperidol prevented the increase of TBARS caused by MK-801. Therefore, we demonstrated that zebrafish might present some behavioral and biochemical features observed in schizophrenia, being considered a promising animal model able to contribute for providing information on potential treatments and disease characteristics.